2020
DOI: 10.1093/biolre/ioaa030
|View full text |Cite
|
Sign up to set email alerts
|

Functional effects of Tribbles homolog 2 in bovine ovarian granulosa cells†

Abstract: Tribbles homologs (TRIB) 1, 2, and 3 represent atypical members of the serine/threonine kinase superfamily. We previously identified TRIB2 as a differentially expressed gene in granulosa cells (GCs) of bovine preovulatory follicles. The current study aimed to further investigate TRIB2 regulation and study its function in the ovary. GCs were collected from follicles at different developmental stages: small antral follicles (SF), dominant follicles (DF) at day 5 of the estrous cycle, and hCG-induced ovulatory fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 72 publications
3
12
0
Order By: Relevance
“…The results confirmed TRIB2 downregulation via CRISPR/Cas9 ( Figure 3A; p < 0.01), while TRIB2 was overexpressed using the pQE system ( Figure 3B; p < 0.01). These data confirming TRIB2 inhibition and overexpression in our model were previously published [14]. Subsequent analyses demonstrated that TRIB2 inhibition did not change CALM1 abundance while TRIB2 overexpression resulted in significant increase in CALM1 abundance ( Figure 4A; p < 0.01).…”
Section: Effects Of Trib2 Inhibition and Overexpression On Its Bindinsupporting
confidence: 91%
See 4 more Smart Citations
“…The results confirmed TRIB2 downregulation via CRISPR/Cas9 ( Figure 3A; p < 0.01), while TRIB2 was overexpressed using the pQE system ( Figure 3B; p < 0.01). These data confirming TRIB2 inhibition and overexpression in our model were previously published [14]. Subsequent analyses demonstrated that TRIB2 inhibition did not change CALM1 abundance while TRIB2 overexpression resulted in significant increase in CALM1 abundance ( Figure 4A; p < 0.01).…”
Section: Effects Of Trib2 Inhibition and Overexpression On Its Bindinsupporting
confidence: 91%
“…Finally, RAB14 displayed a surprising result as both inhibition and overexpression of TRIB2 resulted in increased expression of RAB14 ( Figure 4G). [14]. TRIB2 knockdown was confirmed by RT-qPCR showing that TRIB2 was significantly reduced in GCs via CRISPR/Cas9 as compared to the control and empty vector.…”
Section: Effects Of Trib2 Inhibition and Overexpression On Its Bindinmentioning
confidence: 86%
See 3 more Smart Citations